Analisis Biaya Pokok Produksi (BPP) Dalam Menentukan Harga Jual Sapu Injuk Dan Hasil Laba Penjualan : Studi Kasus UKM Sapu Injuk Desa Muaradua - Meri Luvita; Elan Eriswanto (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
The calculation of the cost of production for SME business actors needs to be carried out or applied as a basis for determining product selling prices and optimal profit amid increasingly fierce market competition and increasing prices of basic commodities which occur as an effort to adjust prices amid frequent fuel price phenomena. go on. This research was conducted to determine the process of determining the cost of production of injuk broom in determining the selling price and profit. The full costing method is the right method to use in this study where all elements of production costs start from raw material costs, labor costs, and factory overhead costs. In determining the selling price that can be determined from the cost of production plus the expected profit. Profit derived from the selling price minus the cost of production. The data were obtained from the results of interviews, observations and documentation conducted by the author to the Sweep Injuk village of Muaradua. Based on the results of the research, it is known that in the calculation of the production cost of production, it has not been included in all the cost components in the production of injuk brooms, so that it affects the setting of selling prices that are not appropriate and the expected profit results are not optimal so far. Then the results are obtained which the researcher can conclude, seen from the calculation of the cost of production using the full costing method tends to be greater.